2000
DOI: 10.1002/(sici)1097-010x(20000101)286:1<36::aid-jez4>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Muscle type-specific myosin isoforms in crustacean muscles

Abstract: Differential expression of multiple myosin heavy chain (MyHC) genes largely determines the diversity of critical physiological, histochemical, and enzymatic properties characteristic of skeletal muscle. Hypotheses to explain myofiber diversity range from intrinsic control of expression based on myoblast lineage to extrinsic control by innervation, hormones, and usage. The unique innervation and specialized function of crayfish (Procambarus clarkii) appendicular and abdominal musculature provide a model to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“…MHCs from different muscle samples were resolved according to the methods of Talmadge and Roy (1993), with the modification that 0.1% β-mercaptoethanol was added to the upper buffer (Blough et al, 1996;LaFramboise, 2000). Samples were separated on 8% resolving gels (50:1 acrylamide:N,N′-methylenebisacrylamide) on 15·cm gels (BioRad Protean II) at 200·V for at least 48·h.…”
Section: Analysis Of Myofibrillar Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…MHCs from different muscle samples were resolved according to the methods of Talmadge and Roy (1993), with the modification that 0.1% β-mercaptoethanol was added to the upper buffer (Blough et al, 1996;LaFramboise, 2000). Samples were separated on 8% resolving gels (50:1 acrylamide:N,N′-methylenebisacrylamide) on 15·cm gels (BioRad Protean II) at 200·V for at least 48·h.…”
Section: Analysis Of Myofibrillar Proteinsmentioning
confidence: 99%
“…S1 fibers have higher myosin ATPase activities than S2 fibers (Mykles, 1988;Neil et al, 1993), which correlates with a twofold higher maximum shortening velocity (Holmes et al, 1999). A recent study of crayfish muscle fiber types identified up to four different MHC proteins (LaFramboise et al, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fur-ther investigations on sensory neurons could relate the mechanisms of neuromodulators to those known at neuromuscular junctions with varying synaptic efficacy Cooper 1995, 1996;LaFramboise et al, 2000). Recently, we have been addressing the influence of these neuromodulators on motor nerve terminals Cooper, 1999, 2000;Griffis et al, 2000;He et al, 1999;Southard et al, 2000) and central integration of sensory input (Strawn et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the relative simplicity of crustacean NMJs and the ability to measure pre-and postsynaptic components discretely, the mechanistic actions of neuromodulators on synaptic plasticity can readily be differentiated. Depending on the particular crustacean skeletal muscle, individual muscle fibers may be innervated by a single phasic or single tonic motor neuron or multiples of both types of motor neurons (Atwood, 1973(Atwood, , 1976Cooper, 1995, 1996a,b;LaFramboise et al, 1999).…”
Section: Introductionmentioning
confidence: 99%